The relationship between the existence of angiographic coronary artery calcification and the severity of coronary artery disease - Kucukdurmaz, Zekeriya; Sezen, Yusuf; Ulas, Turgay; Bas, Memduh; Polat, Mustafa; Yildiz, Ali; Buyukhatipoglu, Hakan; Kaya, Zekeriya; Demirbag, Recep (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
Background: Coronary artery calcification (CAC) is a predictor of coronary artery disease (CAD) and closely related to major adverse cardiac events. The Gensini score is a scoring system to determine the severity and extent of coronary atherosclerosis. Aim : We aimed to investigate the relationship between CAC and both the extent and severity of CAD. Material and methods : Coronary artery calcification was identified by visual examination during fluoroscopic examination. The study population was divided into two groups, according to the presence or absence of CAC. The CAC(+) group consisted of 126 patients (45 women, 81 men), the CAC(–) group 156 patients (58 women, 98 men). Gensini scores were calculated from the results of coronary angiography. Results: We identified CAC more frequently in type 2 diabetes mellitus patients, with no gender differences. Other risk factors for CAD – including age, hypertension, smoking, body mass index, waist circumference, and systolic blood pressure – were not significantly different between the CAC(+) and CAC(–) groups. Serum levels of triglyceride and very low density lipoprotein (VLDL) cholesterol were significantly lower in the CAC(+) group, and diastolic blood pressure levels and type 2 diabetes mellitus (DM) frequency were higher. By logistic regression, an independent relationship was identified between the Gensini score and CAC. Conclusions: Coronary calcification seems to be more prevalent in type 2 DM patients than in the normal population. The Gensini score, that is, the extent and severity of coronary artery disease, appears to be independently related to CAC, an issue that warrants further investigation to allow for future clinical applications.